Padrões hidroquímicos de potabilidade e fatores de contaminação das águas subterrâneas de poços nas adjacências do Campus UFPA – Ananindeua (Icuí-Guajará) - RIBEIRO, Yuri Ribeiro de (2019)
Water is indispensable for living beings, and is used for various purposes. In the last decades the increase of the population accelerated the process of urbanization of several areas without previous preparation, or any infrastructure of sanitation. The concentration of large population groups with low purchasing power in peripheral urban areas is an aspect to be considered, considering that in these areas the use of inadequate practices of disposal of solid wastes and sewage, which contributes to the contamination of surface and underground water sources. These sources, which, by necessity, supply the population itself by direct collection or well drilling. The aim of this study was to evaluate the quality of the aquifer consumed by the population and to characterize them in terms of the drinking standard established by Ministério da Saúde ordinance nº 2.914/2011. Dissemination of the results of the pollutants obtained will allow social contribution to to raise awareness among the residents of the region about the risks of consuming these waters, which will contribute to an improvement in the quality of life through disease prevention. For the evaluation of aquifer quality, the following parameters were analyzed: pH, electrical conductivity, temperature, turbidity, apparent color, acidity, total alkalinity, bicarbonate, total hardness, ammonium, nitrate, sulfate, phosphate, chloride, sodium, potassium, calcium and magnesium. Samples were collected from eight wells in the whole, chosen randomly respecting some distance between them; the depth of the wells varies between 15 and 28 meters. The analyzes were carried out in the laboratory of Hydrochemistry and in the Laboratory of Chromatography of the Institute of Geosciences of the Federal University of Pará (UFPA), where the study indicated that the aquifer exploitation of the region is not adequate, through semi-artesian wells constructed without criteria technical. Strong evidence of septic tank contamination was obtained as a result of inadequate sanitation service. This indicates that the consumption of these waters may lead to health problems for the population.